Historical dictionary of Islamic fundamentalism - Guidere, Mathieu (Historical dictionaries of religions, philosophies, and movements, 2017)
After the rise of the Islamic State in the Middle East and the new geopolitical landscape in this region, it is essential for the modern reader to understand the history that has allowed for and influenced these types of Islamic groups to form. This second edition of Historical Dictionary of Islamic Fundamentalism also contains an introduction, appendixes, an extensive bibliography, and more than 700 cross-referenced entries on ideologies, people, events, and movements of the 20th and 21st centuries.